KETERAMPILAN DASAR MENGAJAR GURU PADA PROSES PEMBELAJARAN MATEMATIKA DI KELAS V SDN 110 PEKANBARU - Nur Ashirin; Lazim N; Zetra Hainul Putra (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2021)
BASIC TEACHING SKILLS FOR TEACHERS IN THE MATHEMATICS LEARNING PROCESS IN CLASS V ELEMENTARY SCHOOL 110 PEKANBARUThis study aims to describe teachers’ basic teaching skills in mathematics learning process of fifth grade students in SDN 110 Pekanbaru. This is a qualitative study conducting in in the even semester of 2019/2020. The subjects of this study were two fifth grade teachers. Teachers’ basic teaching skills were investigated based on four skills, namely asking questions, providing reinforcement, varying learning activities, and guiding small groups and individuals. The results of this study showed that both teachers have sufficient basic teaching skills in mathematics learning process. The teachers performed very well on guiding small groups and individuals comparing to the other skills.